Perbandingan Sistem Kendali Pid Dan Kendali Lqr Pada Sistem Suspensi Aktif Bus (1/4) Menggunakan Simulasi Matlab - Ridwan, Muhammad (Jurnal Sains dan Ilmu Terapan, 2019)
A vehicle suspension system must be able to isolate or reduce the vibration of vehicle body due to unevenness of the road surface. To solve the situation as above, it was needed a controller on the actuator (active suspension) to dampen oscillations of body. In this study, it was designed a controller at a quarter of the suspension system bus using control LQR (Linear Quadratic Regulator) and compared it with PID control. This system will be modeled by State Space and Transfer Function models using Matlab 2011. The results obtained were LQR control system was better than the PID. In LQR, the value of ? was 0.1 and in PID, the value of gain is Kp = 832 100, Ki = 624 075 and 208 025 on the Kd = PID. LQR controller slower reach steady state compared with PID controllers. Stable conditions will be achieved within 30 seconds before the control and after using controller, time of stability to be 3 seconds.